Problematic Cannabis Use and Risk of Complications in Patients with Chronic Hepatitis C - Rashid, Wahida (Cureus, 2019)
Objectives To evaluate the risk of complication in hospitalized chronic hepatitis C (CHC), patients with cannabis use disorder (CUD). Methods We conducted a retrospective study using the nationwide inpatient sample (NIS), and included 31,623 patients (age 15-54) with a primary international classification of diseases, ninth revision (ICD-9) diagnosis for CHC and grouped by co-diagnosis of CUD (1101, 3.5%). Logistic regression model adjusted for confounders was used to evaluate the odds ratio (OR) of CUD and complications during CHC hospitalization. Results Comorbid CUD was prevalent in males (73.2%), Caucasians (59.9%), and from low-income families (65.7%). The most prevalent complications in patients with CUD were ascites (44.9%), alcoholic cirrhosis (42.8%) and non-alcoholic cirrhosis (41.1%). The odds of association for hepatic encephalopathy was 2.2 times higher (95% CI 1.477-3.350) in 2.8% CHC inpatients with CUD compared to 1.2% non-CUD inpatients. Hepatic encephalopathy had higher odds of association with a male by 1.4 times (95% CI 1.094-1.760), and African American by 1.7 times (95% CI 1.293-2.259). Conclusion CUD is significantly associated with 122% increased likelihood for hepatic encephalopathy that may worsen overall hospitalization outcomes in CHC patients. Hence, we need to consider the complex relationship between CUD and CHC and manage them optimally to improve the health-related quality of life.